2020
DOI: 10.22495/cocv17i4art3
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of GCC firms’ stock returns to exchange rate, interest rate, and oil price volatility

Abstract: This study seeks to investigate the sensitivity of stock returns to exchange rate, interest rate and oil price volatility in the Gulf Cooperation Council (GCC) countries. It employs both the multivariate ordinary least square (OLS) regression and the exponential generalized autoregressive conditional heteroscedastic in mean (EGARCH-M) models to analyse the data collected from Bloomberg and DataStream on the GCC countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates) for the period J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Ultimately, the findings of the study indicate that oil prices and other macroeconomic determinants have a significant impact on stock prices. This paper contributes in the existing literature in the GCC region by providing an understanding of stock markets from a macroeconomic perspective, which is shown to support previous studies on the same subject in the GCC, such as of Alenezi et al, (2020).…”
Section: Introductionsupporting
confidence: 75%
“…Ultimately, the findings of the study indicate that oil prices and other macroeconomic determinants have a significant impact on stock prices. This paper contributes in the existing literature in the GCC region by providing an understanding of stock markets from a macroeconomic perspective, which is shown to support previous studies on the same subject in the GCC, such as of Alenezi et al, (2020).…”
Section: Introductionsupporting
confidence: 75%
“…Macroeconomic factors include, but are not limited to interest rates, exchange rates, oil prices, and the money supply. A recent study conducted about firms in the Gulf Cooperation Council (GCC), which used three parameters (exchange rates, interest rates, and oil prices) to investigate their relationship to stock returns, suggested that the results vary from one industry to another (Alenezi et al, 2020). In Kuwait, financial firms were less exposed to fluctuations in exchange and interest rates than nonfinancial firms.…”
Section: Literature Reviewmentioning
confidence: 99%